2016
DOI: 10.3390/rs8110896
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range WindScanner System

Abstract: Abstract:The technical aspects of a multi-Doppler LiDAR instrument, the long-range WindScanner system, are presented accompanied by an overview of the results from several field campaigns. The long-range WindScanner system consists of three spatially-separated, scanning coherent Doppler LiDARs and a remote master computer that coordinates them. The LiDARs were carefully engineered to perform user-defined and time-controlled scanning trajectories. Their wireless coordination via the master computer allows achie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 45 publications
3
91
0
1
Order By: Relevance
“…Under the WindScanner.dk project, DTU Wind Energy, with the expert support from specialized industrial partners, developed scanner heads, converting the profiling lidars into the scanning lidars that make up the LRWS and SRWS. In addition to the hardware developments, DTU Wind Energy developed specific software solutions for both WindScanner systems (e.g., Vasiljević et al, 2016a).…”
Section: Windscanner Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the WindScanner.dk project, DTU Wind Energy, with the expert support from specialized industrial partners, developed scanner heads, converting the profiling lidars into the scanning lidars that make up the LRWS and SRWS. In addition to the hardware developments, DTU Wind Energy developed specific software solutions for both WindScanner systems (e.g., Vasiljević et al, 2016a).…”
Section: Windscanner Systemsmentioning
confidence: 99%
“…As discussed in Vasiljević et al (2016a), lidars in the previously mentioned studies were individually configured, run and monitored; thus, there was no central computer that would ensure their synchronicity. Also, commercially available lidars were used in the majority of these studies, and the configuration flexibility and available auxiliary information of such devices is usually limited (e.g., no accurate timing of scans and only simple scanning methods are available).…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional wind-field measurements made using dual-Doppler intersecting RHI scans and using continuity to estimate the vertical velocity were used to study flow upstream and downstream of a utility-scale wind turbine . Three-dimensional wind and turbulence measurements using fully coordinated short-range continuous wave triple lidars (Mikkelsen et al, 2008;Simley et al, 2016) and long-range triple lidar scanning Vasiljević et al, 2016) have been demonstrated to provide high quality measurements of complex flow. In addition, manually coordinated triple lidar measurements (Wang et al, 2016) were also tested and showed promise in measuring the 3-D wind fields operationally.…”
Section: Introductionmentioning
confidence: 99%
“…Except in the cases of co-located synchronised measurements (e.g. WindScanner (Vasiljevic et al, 2016) or multi-static systems), the different LOS velocities result from probing the wind in several locations; therefore, assumptions on the wind flow must be made.…”
Section: Wind Measurements With Doppler Lidarsmentioning
confidence: 99%